AGROTOURISM ENVIRONMENTAL PERFORMANCE EVALUATION WITH THE "APOIA-NOVORURAL" ENVIRONMENTAL IMPACT ASSESSMENT SYSTEM - Ramos Filho, Luiz Octávio; Rodrigues, Isis; Toyoko Shiraishi Frighetto, Rosa; Stachetti Rodrigues, Geraldo; Campanhola, Clayton; Brombal, José Carlos (Science & Technology Journals, 2004)
This study aimed at evaluating the environmental performance of agrotourism, by applying the "Weighed Environmental Impact Assessment of New Rural Activities" System (APOIA-NovoRural). The System integrates the assessment dimensions of landscape ecology, environmental quality (soil, water and atmosphere), sociocultural values, economic values, and management/administration, offering an objective and comprehensive measure of the contribution of a given rural activity (in the present case, agrotourism) at the rural establishment level, towards the local sustainable development. The APOIA-NovoRural System was applied in ten rural establishments of the Itu region (interior of São Paulo State). In general the agrotourism activity showed good economic performance and excellent results for the water quality indicators. On the other hand, several aspects relative to landscape and natural habitat conservation, as well as those relative to management/administration are shown to need improvements. The results obtained with the study allow the indication of the main aspects of the activity that may be failing to comply with defined environmental benchmarks, facilitating the selection of management alternatives, with the objective of improving the contributions of agrotourism to the local sustainable development.